Ethnomatematics: Treasure Search Activity in the Musi River - Malalina Malalina; Ratu Ilma Indra Putri; Zulkardi Zulkardi; Yusuf Hartono (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2020)
Ethnomathematic is one of mathematics learning innovations which integrate cultures to preserve local cultural values. A treasure quest at Musi River Palembang is included as a culture because it is the community activity with its unique characteristic carried out at Musi River to meet the necessities of life, and is passed down from one generation to the next generation. The research aims to explain aspects of mathematical computation to treasure quest at Musi River Palembang. A literature study is a method used in this research. Firstly, formulating research problem was how the mathematical aspects connect to the finding of treasure quest at Musi River Palembang. Then, literature related to the problem of the study was reviewed. The next step was evaluating data based on the literature to answer the research problem. After that, data analysis was conducted. Descriptive analysis was used to analyze the data. Lastly, the data was interpreted to obtain a conclusion. The interpretation showed that the treasure quest at Musi River had mathematical counting aspects namely, counting the number of human resources in a treasure quest group; counting the wages for each person in the team based on his or her duties; counting expenses required for a treasure quest; counting the number of objects obtained, and determining the sale price of the objects. The activity also contained a mathematical concept in the mathematics learning of some subjects at VII grade of junior high school level namely, the operation of the material count, social arithmetic, and sets